The Use of Buyer Concentration Ratios in Tests of Oligopoly Models - Guth, Louis A.; Schwartz, Robert A.; Whitcomb, David K. (The Review of Economics and Statistics, 1976)
provide a valuable stimulus to competition beca'use of their insensitivity both to the overall level of entry barriers and to several of the entry barriers taken separately.16 Such a stimulus might be decreed of significant benefit to Canada by the Foreign Policy Review Agency, whlich screens all new foreign direct investment in Canada. However, should this stimulus be givep relatively little weight by the agency, then the composition of entrants into Canadian manufacturing industries is likely to change such that the overall level of entry barriers will be raised substantially.17